Percutaneous Image-Guided Biopsy of the Pancreas - McRae, Stephen (Digestive Disease Interventions, 2018)
Percutaneous image-guided biopsy of the pancreas is a safe, effective, efficient, and minimally invasive way to obtain samples for pathological diagnosis of pancreatic mass lesions. The myriad of diseases that can involve the pancreas require different therapies. Therefore, pathological diagnosis is key. With proper imaging resources and techniques, most mass lesions of the pancreas that are visible on cross-sectional imaging can be approached safely and accurately percutaneously under either computed tomography (CT) or ultrasound guidance. These lesions may be accessed through anterior, posterior, and/or lateral approaches depending upon their proximity to the anticipated skin puncture site, and the presence or absence of intervening structures. While the ideal percutaneous route to any pancreatic target lesion is the one that has no vital structures in its path, methods and tools exist to make even the most seemingly obstructed paths to pancreatic targets navigable. Once accessed, the targets may be sampled by either fine-needle aspiration or core needle biopsy. The alternatives to percutaneous image-guided biopsy of the pancreas include open (surgical) biopsy and endoscopic ultrasound-guided (EUS) biopsy. Percutaneous image-guided biopsy poses less risk to the patient than open biopsy and has been shown to be as accurate as EUS biopsy with an even lower complication rate.
Keywords: percutaneous; pancreas